Research of drying of brewer pellets aimed at increasing of its efficiency and lowering of power consumption - Sukmanov, Valeriy; Bessarab, Alexander; Shutyuk, Vitaliy; Stefanov, Stefan (My University, 2016)
This paper presents the results of research of the drying process in the brewer pellets in aerovibrofluidized bed. The kinetics of drying of pellets in the suspension bed has been experimentally studied. We have received the generalized drying curve of brewer pellets at different process conditions. The generalized drying curve received as a collocation of the drying curves of brewer pellets at different process conditions is an indication of constant value of speed multiplied by time of drying, which simplifies the calculations of changes in moisture content during certain periods of the heat treatment of the product.We offered the relative ratio of energy consumption; proportionality factor of performance and bed depth; qualified expenditure power consumption indicator, which allow to reasonably choose conditions of brewer pellets drying and significantly improve the value of energy saving performance indicators of the drying process. There have also been introduced the parameters of qualified expenditure power consumption and the non-dimentional coefficient of power consumption.
Keywords: drying; aerovibrofluidized bed; brewer pellets; energy efficiency; сушіння; віброкиплячий шар; пивна дробина; енергоефективність; кафедра технології консервування